2018
DOI: 10.3762/bjnano.9.179
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of hafnium nanoparticles and hafnium nanoparticle films by gas condensation and energetic deposition

Abstract: In this work we study the fabrication and characterization of hafnium nanoparticles and hafnium nanoparticle thin films. Hafnium nanoparticles were grown in vacuum by magnetron-sputtering inert-gas condensation. The as deposited nanoparticles have a hexagonal close-packed crystal structure, they possess truncated hexagonal biprism shape and are prone to surface oxidation when exposed to ambient air forming core–shell Hf/HfO2 structures. Hafnium nanoparticle thin films were formed through energetic nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 74 publications
0
6
0
2
Order By: Relevance
“…Figure 40(a) shows that it is possible to obtain a high aspect ratio nanostructured tower-like structure using the lens system. Michelakaki et al (Michelakaki, et al, 2018) demonstrated that the porosity of the film prepared by this nanoparticle beam cluster technique can be significantly improved by applying voltage on the substrate. A fine pattern as small as 400 nm linewidth was realized by adapting lithography process as shown in Fig.…”
Section: Nanoparticles Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 40(a) shows that it is possible to obtain a high aspect ratio nanostructured tower-like structure using the lens system. Michelakaki et al (Michelakaki, et al, 2018) demonstrated that the porosity of the film prepared by this nanoparticle beam cluster technique can be significantly improved by applying voltage on the substrate. A fine pattern as small as 400 nm linewidth was realized by adapting lithography process as shown in Fig.…”
Section: Nanoparticles Assemblymentioning
confidence: 99%
“…40 SEM image (a) Tower-like 3D structure formation of SiC nanoparticles deposited by focused particle beam on a stationary substrate (Hafiz, et al, 2006b), 3D patterns composed of Hf nanoparticles deposited at a substrate voltage of Vs = 4.5 kV: (b) The high-magnification image shows the granular structure of these patterns; (c,d) the areas that appear white are structures formed from the nanoparticles. Large square structures of 5 μm size were successfully constructed (e) Cohesive structure with 1 μm side found at a random position on the substrate (Michelakaki, et al, 2018).…”
Section: Nanoparticles Assemblymentioning
confidence: 99%
“…One of the many techniques, which pioneered the research on nanomaterials, is the inert gas condensation (IGC) method. [1][2][3][4][5][6][7][8][9][10] In the original version of the IGC method, the material of choice is evaporated from a resistively heated refractory metal crucible (W, Ta, Mo) inside an ultrahigh vacuum (UHV) chamber, which is backlled with a low pressure (typically between 1 and 20 mbar) of an inert gas or a gas mixture. 11,12 The type of inert gas (He, Ar, Ne), the pressure of the inert gas and the vapor pressure of the evaporating species (depending on the temperature of the evaporated material) are the main parameters to control the size and size distribution of the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Ως εκ τούτου, η διερεύνηση της σύνθεσης και των ιδιοτήτων τέτοιων υμενίων μπορεί να παρουσιάσει ενδιαφέρον σε διάφορες εφαρμογές της μικροτεχνολογίας. Οι ιδιότητες των υλικών διερευνώνται μέσω συνδυασμού της μεθόδου περίθλασης ακτίνων Χ (Xray Diffraction, XRD), της μικροσκοπίας διέλευσης ηλεκτρονίων (Transmission Electron Microscopy, ΤΕΜ), της μικροσκοπίας ατομικής δύναμης (Atomic Force Microscopy, AFM), των τεχνικών νανοδιείσδυσης και χαρακτηρισμού Van der Pauw 266 .…”
Section: αντίσταση στην εγχάραξη των επιφανειών Ps / Pmmaunclassified
“…Οι δομικές, μηχανικές και ηλεκτρικές ιδιότητες λεπτών υμενίων αφνίου διερευνώνται ως συνάρτηση του πεδίου επιτάχυνσης των νανοσωματιδίων. Συνοψίζοντας, παρατηρείται ότι τα υμένια αυτά μπορούν να σχεδιαστούν στο υποστρώμα σε διαστάσεις υπομικρών (submicron), χρησιμοποιώντας συμβατική λιθογραφία ενώ το πορώδες τους μπορεί να ελεγχθεί από το πεδίο επιτάχυνσης ανοίγοντας το δρόμο για τις εφαρμογές τους σε μικρο-συσκευές 247 .…”
Section: γενικά σχόλιαunclassified